Sonic Hedgehog signalling in the regulation of barrier tissue homeostasis and inflammation. (17th October 2021) - Lau, Ching‐In; Yánez, Diana C.; Papaioannou, Eleftheria; Ross, Susan; Crompton, Tessa
Abstract : Epithelial barrier tissues such as the skin and airway form an essential interface between the mammalian host and its external environment. These physical barriers are crucial to prevent damage and disease from environmental insults and allergens. Failure to maintain barrier function against such risks can lead to severe inflammatory disorders, including atopic dermatitis and asthma. Here, we discuss the role of the morphogen Sonic Hedgehog in postnatal skin and lung and the impact of Shh signalling on repair, inflammation, and atopic disease in these tissues. Abstract : Shh‐mediated crosstalk between epithelial tissues and immune cells under homeostatic and inflammatory conditions. The low levels of Shh in the epithelium under homeostasis serve as a critical factor for the maintenance of tissue barrier integrity and immune function. Under inflammatory conditions, increased secretion of Shh by epithelium ensues driving activation and differentiation of innate and adaptive immune cells influencing tissue repair and inflammation.